A fluorescent turn-on probe for cyanide anion detection based on an AIE active cobalt(ii) complex. Issue 6 (22nd January 2018) - Gabr, Moustafa T.; Pigge, F. Christopher
Abstract : A Co(ii ) complex based on an AIE-active tetraarylethylene ligand displays selective fluorescence enhancement in the presence of cyanide anion in aqueous solution. Abstract : A new tetradentate polypyridine ligand that displays aggregation induced emission (AIE) characteristics has been synthesized. A coordination complex with CoCl2 has been prepared and characterized by X-ray crystallography. The Co(ii ) complex retains the AIE activity of the ligand in aqueous solution while also exhibiting a selective turn-on fluorescence response in the presence of cyanide anion. A complex : CN − binding stoichiometry of 1 : 2 was indicated via Job plot analysis and the limit of detection for CN − was determined to be 0.59 μM. The fluorescence response is attributed to coordination of CN − by the AIE active Co(ii ) complex, resulting in decreased solubility in aqueous medium and concomitant generation of larger nanoaggregates as revealed by dynamic light scattering (DLS) measurements. The sensitivity and selectivity displayed by this sensor for CN − over other anions renders it a candidate probe for CN − detection in aqueous environments.